The effect of health literacy, psychological resilience, and internet addiction levels on the fear of COVID-19 in healthcare professionals. - Aydin, Aykut; Aydin Sayilan, Aylin; Kulakac, Nursen (Work, 2025)
Background: Healthcare professionals are known to make intensive use of the internet to improve their health literacy, preserve their psychological resilience, resolve uncertainties, and lessen their fear of COVID-19. Although several studies have addressed these concepts, we encountered none examining their relationships with one another. Objective: This research set out to determine the effects of health literacy, psychological resilience, and internet addiction levels on the fear of COVID-19 in healthcare professionals. Methods: The sample in this descriptive, cross-sectional, and correlation-seeking research consisted of 456 health workers. The data were collected using an information form and the Health Literacy Scale (HLS), the Brief Resilience Scale (BRS), Young's Internet Addiction Test-Short Form (YIAT-SF), and the Fear of COVID-19 Scale. Results: The mean age of the health professionals enrolled in the research was 40.80 ± 11.39 years (min 22, max 68), 52.4% were women, 87.1% held bachelor's degrees, 86.8% were married, and 5.9% were working as nurses. The participants' mean scale scores were 54.97 ± 5.62 for the HLS, 26.95 ± 9.57 for YIAT-SF, 20.57 ± 3.62 for the BRS, and 20.33 ± 2.97 for the Fear of COVID-19 Scale. Conclusions: The healthcare professionals in this study exhibited adequate levels of health literacy and psychological resilience, a moderate level of internet addiction, and still experienced fear of COVID-19. Health literacy, internet addiction, and psychological well-being emerged as important factors in the fear of COVID-19.